Excavation model of soil sampling device based on particle image velocimetry. (December 2015) - Mori, Daiki; Ishigami, Genya
Highlights: Energy-efficient strategy for sampling Martian subsurface soil is proposed. End-effector shape suitable for subsurface soil sampling is determined. A soil–tool interaction model is formulated based on particle image velocimetry. The interaction model calculates the forces and torque during the sampling procedure. The interaction model estimates the energy consumption and the most efficient tool size. Abstract: This work aims to establish an energy-efficient strategy for sampling Martian subsurface soil for future extraterrestrial-life exploration missions. To this end, requirements for a robotic arm are carefully examined and an end-effector shape suitable for subsurface soil sampling is determined. A soil–tool interaction model is formulated based soil-flow measured by particle image velocimetry (PIV). The proposed model calculates the resistance forces and torque generated during the sampling procedure and is validated through a comparison of experimental data obtained from the force sensor and numerical data calculated from the proposed model. Results indicate that the proposed model provides an accurate estimation of the force generated during soil sampling. Furthermore, the interaction model is capable of estimating the robotic arm's energy consumption and calculating the most efficient tool size to use.